1979
DOI: 10.1128/aac.16.5.592
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of cefotaxime

Abstract: The pharmacokinetics of cefotaxime after intramuscular injection and intravenous infusion were determined. The mean peak serum level after the 500-mg intramuscular dose was 11.7 ,ug/ml, and it was 20.5 ,ug/ml after a 1,000-mg dose.The serum half-life was 1.2 and 1.3 h, respectively for the two doses. The apparent fractional volumes of distribution of 32 and 37 liters were All subjects were judged healthy on the basis of history, physical examinations, chemistry profile (SMA 12/60; Technicon), complete blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
26
1

Year Published

1981
1981
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(36 citation statements)
references
References 10 publications
9
26
1
Order By: Relevance
“…The major route of elimination for moxalactam is via the kidneys. We found a mean of 61% in the urine, which is similar to the 55 to 76% reported by others (24,29,32,35 (7,9,10,12,22) and 76.1 min calculated from our own data, is much more rapid than that of cefoperazone (1,6,33,34) and moxalactam (19,29,35,36 Elimination of cefotaxime is rapid, with about 90% of the dose recovered in urine by HPLC, of which two-thirds is detected as unchanged cefotaxime and one-third as the major metabolite desacetyl cefotaxime. Bax et al (2) reported a total urine recovery of 87% with 35% as desacetylated metabolite, compared with a total recovery rate of 89.6% with 29.1% as metabolite in our study.…”
Section: Methodssupporting
confidence: 77%
See 1 more Smart Citation
“…The major route of elimination for moxalactam is via the kidneys. We found a mean of 61% in the urine, which is similar to the 55 to 76% reported by others (24,29,32,35 (7,9,10,12,22) and 76.1 min calculated from our own data, is much more rapid than that of cefoperazone (1,6,33,34) and moxalactam (19,29,35,36 Elimination of cefotaxime is rapid, with about 90% of the dose recovered in urine by HPLC, of which two-thirds is detected as unchanged cefotaxime and one-third as the major metabolite desacetyl cefotaxime. Bax et al (2) reported a total urine recovery of 87% with 35% as desacetylated metabolite, compared with a total recovery rate of 89.6% with 29.1% as metabolite in our study.…”
Section: Methodssupporting
confidence: 77%
“…Blood samples were taken over 12 h: before injection; after 5,10,20,30, and 45 min; and after 1, 1.5, 2, 3, 4, 6, 8, and 12 h. Blood specimens were centrifuged at 4°C after clotting at room temperature. Urine was collected 0 to 3, 3 to 6, 6 to Urinary excretion.…”
Section: Methodsmentioning
confidence: 99%
“…The human pharmacology of cefotaxime is similar to that of most currently available cephalosporins, but its half-life of approximately 1 h is twice as long as that of cephalothin (7,14,19). The serum levels after 1 g (Table 3) are in agreement with previously published findings, including the presence of residual antimicrobial activity up to 6 h after dosing (8,14,19 levels for up to 6 h after i.v.…”
Section: Discussionmentioning
confidence: 85%
“…The pharmacokinetic parameters after single injection have been presented in several species such as rats (3), sheep (4), goats (5), calves (6), cats (7), dogs (8), and humans (9). An approximate serum half-life of 1.1-1.3 h after injection was confirmed in different studies (10)(11)(12)(13). The drug is primarily eliminated by the kidney, but also converted into the less active metabolite desacetyl-cefotaxime in the liver to a significant level (14)(15).…”
Section: Introductionmentioning
confidence: 86%